2019
DOI: 10.1021/acscatal.9b00421
|View full text |Cite
|
Sign up to set email alerts
|

Ceria Nanocrystals Supporting Pd for Formic Acid Electrocatalytic Oxidation: Prominent Polar Surface Metal Support Interactions

Abstract: Ceria has been widely used as support in electrocatalysis for its high degree of oxygen storage, fast oxygen mobility, and reduction and oxidation properties at mild conditions. However, it is unclear what are the underlying principles and the nature of surface involved. By controlling the growth of various morphologies of ceria nanoparticles, it is demonstrated that the cubic-form of ceria, predominantly covered with higher energy polar surface (100), as support for Pd gives much higher activity in the electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…In addition to the foreign metal modification, the enhanced catalytic performance is mainly attributed to the high-index The catalytic performance for the electro-oxidation of formic acid can also be improved by taking advantage of the interaction between metal and suitable substrate. 12 For example, Wang et al reported the atomic dispersion of Pt on mesoporous sulfur-doped carbon (meso_S-C) with Pt loading as high as up to 10% by a H 2 thermal reduction process ( Fig. 3c-e).…”
Section: Pt-and Pd-based Electrocatalysts For Formic Acid Oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the foreign metal modification, the enhanced catalytic performance is mainly attributed to the high-index The catalytic performance for the electro-oxidation of formic acid can also be improved by taking advantage of the interaction between metal and suitable substrate. 12 For example, Wang et al reported the atomic dispersion of Pt on mesoporous sulfur-doped carbon (meso_S-C) with Pt loading as high as up to 10% by a H 2 thermal reduction process ( Fig. 3c-e).…”
Section: Pt-and Pd-based Electrocatalysts For Formic Acid Oxidationmentioning
confidence: 99%
“…The low formic acid crossover allows to using high concentration of formic acid as fuel, which compensates for the lower energy density of formic acid compared to other liquid fuels. [12][13][14] Moreover, the theoretical open have been achieved in the above mentioned two aspects for formic acid oxidation, i.e. reaction mechanism and electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Pd/CeO2 nanocubes with dominant polar (100) facet exposure shows at least 2 times higher activity than the other non-polar CeO2 samples in (electro)catalytic reactions, which also appears to be less susceptible to CO poisoning. 16 Operando ambient pressure (AP) XPS showed that in Pd/CeO2 nanocubes, the Ce 3+ /Ce 4+ ratio was maintained at around 0.3 regardless of whether in reduction or oxidation environments, and the conversion between Pd(0) and Pd(II) was also suppressed, suggesting the high oxygen mobility of polar CeO2 and fast Ce 4+ /Ce 3+ redox pair can resist the change of oxidation states in overlying metal. 16 More detailed study of the Pd/CeO2 nanocubes system was then performed with the help of electron energy loss spectroscopy -9h).…”
Section: Fast Oxygen Mobility Of Faceted Ceo2 Nanomaterialsmentioning
confidence: 99%
“…16 Operando ambient pressure (AP) XPS showed that in Pd/CeO2 nanocubes, the Ce 3+ /Ce 4+ ratio was maintained at around 0.3 regardless of whether in reduction or oxidation environments, and the conversion between Pd(0) and Pd(II) was also suppressed, suggesting the high oxygen mobility of polar CeO2 and fast Ce 4+ /Ce 3+ redox pair can resist the change of oxidation states in overlying metal. 16 More detailed study of the Pd/CeO2 nanocubes system was then performed with the help of electron energy loss spectroscopy -9h). 35 The effects arisen from the Ce 4+ /Ce 3+ redox pair was also supported by the TMP probe-assisted ssNMR measurements.…”
Section: Fast Oxygen Mobility Of Faceted Ceo2 Nanomaterialsmentioning
confidence: 99%
“…Figure S8. (A) Exit wave restoration image of polar-faceted CeO2 nanocubes with predominant polar (100) surfaces where deviations to hexagonal shape with reconstructed (111) facets can be seen; (B) High magnification of the exit wave restoration showing the (100) showing discrete alternative atomic layers of Ce 3+ /Ce 4+ and O 2ions can be visualized and indexed matching with corresponding (100) model; (C) TEM image of CeO2 nanorods; (D) predominant non-polar (110) surface with inter-dispersed Ce cations and O anions but also containing small degrees of other reconstructed surfaces of (111) and (100) surfaces[13].…”
mentioning
confidence: 99%